Factors contributing to academic stress among first-year EFL university students - Citra Dwi Safitri; Seny Luhriyani Sunusi; Muhammad Fahri Jaya Sudding; Andi Hajar (Privietlab, 2026)
Academic stress is a common challenge among first-year university students, particularly those studying in English based study programs, where academic and language-related demands coexist. This study aimed to explore the factors contributing to academic stress among first-year EFL university students. Employing a qualitative descriptive design, the study involved 39 first-year EFL students at Program Studi Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar. Data were collected through open-ended questionnaires and semi-structured interviews and analyzed using Braun and Clarke's thematic analysis. The findings revealed four major factors contributing to academic stress: time management challenges, heavy academic workload and assignment demands, adaptation to independent learning, and adjustment to the English-language learning environment. Time management emerged as the most dominant factor, followed by academic workload, indicating that students struggled to balance multiple academic responsibilities while adapting to greater learning autonomy. Participants also reported difficulties adjusting to self-directed learning and coping with English-mediated instruction, which required additional cognitive and linguistic effort. The study contributes to the understanding of academic stress in EFL higher education by highlighting the interaction between general university adjustment and language-related challenges. The findings underscore the importance of institutional support, including orientation programs, time-management training, self-regulated learning development, and language support initiatives to facilitate students' academic transition and well-being. Keywords: academic stress, first-year university students, EFL students, qualitative descriptive research, higher education.